2016
DOI: 10.1039/c6cp04345c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic nuclear polarisation by thermal mixing: quantum theory and macroscopic simulations

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk J o u r n a l Na me A theory of dynamic nuclear polarisation (DNP) by thermal mixing is suggested based on purely quantum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…The dispersion parameter plays an important role of breaking the symmetry in the Hamiltonian by shifting one electron spin frequency with respect to the other, as was previously discussed for regular TM mechanism 18 . When the dispersion parameter = 0, the effective spin system Hamiltonian shown in eqns (7)(8)( 9) is symmetric with respect to swapping 1 and 2 operators, making the two electron spins indistinguishable.…”
Section: Quantum Mechanical Model Of Heteronuclear Dnpmentioning
confidence: 90%
See 1 more Smart Citation
“…The dispersion parameter plays an important role of breaking the symmetry in the Hamiltonian by shifting one electron spin frequency with respect to the other, as was previously discussed for regular TM mechanism 18 . When the dispersion parameter = 0, the effective spin system Hamiltonian shown in eqns (7)(8)( 9) is symmetric with respect to swapping 1 and 2 operators, making the two electron spins indistinguishable.…”
Section: Quantum Mechanical Model Of Heteronuclear Dnpmentioning
confidence: 90%
“…Therefore, thermodynamically speaking, the two types of nuclei are in the indirect thermal contact with one another, leading to an observable polarization exchange between the two 11,16 . Recently, however, thermal mixing was also treated using models based on density matrix formalism 17,18 . In particular, the emergence of a common spin temperature in the dipolar reservoir of strongly coupled electron spins has been confirmed by the simulations 17 , which provides support for this concept, crucial to the thermodynamic description of TM-mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the degree of order and symmetries within the sample structure, D kk and D kk can either be well defined (e.g., for crystals) or considered to be random (e.g., for glasses). In amorphous materials ∆ k are also distributed due to the anisotropic interaction of the electrons with the static field, leading to inhomogeneous broadening of the EPR line [3,13,24]. Dissipative processes within the electron system are 1. (a) Steady-state polarization spectrapz(∆) obtained by the mean-field formula (6) (solid lines) and the numerically exact solution (dashed lines) for N = 4, D = 10 MHz, R2 = 10 6 s −1 and different temperature and microwave parameters: p = 0.11, ω1 = 75 kHz, R1 = 10 3 s −1 (red); p = 0.55, ω1 = 12 kHz, R1 = 10 s −1 (green); p = 0.99, ω1 = 7 kHz, R1 = 1 s −1 (blue).…”
mentioning
confidence: 99%
“…Insight into the dynamics of strongly coupled, microwave driven electronic ensembles is also needed in order to improve our understanding of dynamic nuclear polarization (DNP), which is an out-of-equilibrium technique to enhance the sensitivity of nuclear magnetic resonance (NMR) applications by orders of magnitude (see, e.g., Ref. [4][5][6]) -in particular, this concerns the cross effect and thermal mixing DNP mechanisms [7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…Guarin et al characterized the TM-DNP using the nitroxide radicals at 3.5 T144 and Jähning et al investigated the TM in different nitroxide radical concentration at 3.5 T and 7 T 145 . Karabanov and coworkers described the quantum mechanics of TM-DNP and predicted that the strong asymmetry in the e-e coupling is essential for the efficient TM based polarization transfer 146. Kundu and coworkers further suggested that electron-electron double resonance (ELDOR) can be employed to identify the TM-DNP mechanism and differentiate between the CE and the TM 147.…”
mentioning
confidence: 99%